2016
DOI: 10.1682/jrrd.2014.11.0295
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate assessment of subjective and objective measures of social and family satisfaction in Veterans with history of traumatic brain injury

Abstract: Abstract-Approximately 20% of current-era Veterans have sustained a traumatic brain injury (TBI), which can result in persistent postconcussive symptoms. These symptoms may disrupt family and social functioning. We explored psychiatric, postconcussive, and cognitive factors as correlates of objective functioning and subjective satisfaction in family and social relationships. At entry into a supported employment study, 50 unemployed Veterans with a history of mild to moderate TBI and current cognitive impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…Para Off e colaboradores 19 , é a partir desses impactos físicos, emocionais e sociais que o cuidador sofre mudanças significativas no bem-estar e qualidade de vida. Os resultados do estudo supracitado estão em consonância com as evidências identificadas na presente pesquisa, enfatizando a importância de um modelo teórico e terminológico que embase o cuidado de enfermagem.…”
Section: Resultsunclassified
“…Para Off e colaboradores 19 , é a partir desses impactos físicos, emocionais e sociais que o cuidador sofre mudanças significativas no bem-estar e qualidade de vida. Os resultados do estudo supracitado estão em consonância com as evidências identificadas na presente pesquisa, enfatizando a importância de um modelo teórico e terminológico que embase o cuidado de enfermagem.…”
Section: Resultsunclassified
“…While these two constructs are conceptually distinct, this relationship is unsurprising and aligns with the findings of a previous study examining the relationship between depressive symptoms and enfranchisement, 19 and other studies examining the relationship between depressive symptoms and community participation more generally. [20][21][22] If one does not feel a sense of inclusion and connection with the community, this may contribute to a lower sense of fulfillment or enjoyment in life, resulting in higher rates of depressive symptoms. It is also possible that individuals with depressive symptoms may not initiate community activities and engagement that would lead to greater experience of enfranchisement.…”
Section: Discussionmentioning
confidence: 99%
“…The weak relationships between enfranchisement and cognition and physical functioning are interesting, because physical function and cognition are impairments that are often the focus of rehabilitation interventions. 21,22,[24][25][26] The stronger relationship between enfranchisement and social support may be what matters more than these specific impairments. Perhaps, individualized social support can address the challenges imposed by varying degrees of impairments in cognitive and physical functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition (the executive functioning skill that the Stroop assesses) has been found to be related to face emotion perception in major depression disorder, whereas other aspects of executive functioning skills (including verbal fluency) were not (72). Other studies have shown that verbal fluency deficits relate to decreased social contact post-TBI (73), emphasizing one such role for this executive function skill in social cognition. One way to unify our results, under a well-accepted model of social cognition, is to examine how they differentiate 'hot' and 'cold' processes.…”
Section: Re-validating the Importance Of Executive Function Skills Fo...mentioning
confidence: 99%